REPRESENTASI GAMBARAN ALAM PADA PERWUJUDAN ARSITEKTUR PADMASANA DI BALI - Paramadhyaksa, I Nyoman Widya (Bumi Lestari; Vol 12 No 2 (2012), 2012)
The padmasana shrine is one of the main holy structures of Balinese Hindu. This shrine hasvarious ornaments, decorative elements and other forms that have symbolic meanings. Thesymbolic contents in padmasana have close relation with mythology and the concepts ofHindu teaching. Beside that, the concepts of architectural representation of padmasana alsohave a correlation with the nature representation of the earth. This article discusses about therepresentation of padmasana shrine as the symbol of mountain and the representation ofnature on earth.
Keywords: padmasana; Balinese Hindu shrine; ornament; representation; nature.